2019
DOI: 10.1017/cts.2019.389
|View full text |Cite
|
Sign up to set email alerts
|

Community advisory boards: Experiences and common practices of clinical and translational science award programs

Abstract: Community advisory boards (CABs) are a valuable strategy for engaging and partnering with communities in research. Eighty-nine percent of Clinical and Translational Science Awardees (CTSA) responding to a 2011 survey reported having a CAB. CTSAs’ experiences with CABs are valuable for informing future practice. This study was conducted to describe common CAB implementation practices among CTSAs; document perceived benefits, challenges, and contributions; and examine their progress toward desirable outcomes. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 9 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…A 2011 survey of Clinical and Translational Science Awards programs found that 89% worked with CABs, 97 and recently, common practices have been articulated. 98 Likewise, the National Cancer Institute explicitly referenced CAB development as an engagement practice in their 2016 mandate for "community outreach and engagement" within National Cancer Institute-designated cancer centers. 99 Finally, the Patient-Centered Outcomes Research Institute developed an expectation for stakeholder engagement as a central tenet of their grant making.…”
Section: Discussionmentioning
confidence: 99%
“…A 2011 survey of Clinical and Translational Science Awards programs found that 89% worked with CABs, 97 and recently, common practices have been articulated. 98 Likewise, the National Cancer Institute explicitly referenced CAB development as an engagement practice in their 2016 mandate for "community outreach and engagement" within National Cancer Institute-designated cancer centers. 99 Finally, the Patient-Centered Outcomes Research Institute developed an expectation for stakeholder engagement as a central tenet of their grant making.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Community and stakeholder advisory councils or boards have been established as an effective strategy to develop research that is responsive and relevant to the end-users. [16] The infrastructure of a stakeholder advisory council may be an effective approach to engage persons living with dementia and family care partners in research alongside health and social care professionals. Stakeholder advisory councils that include family care partners have been shown to be effective in informing the development and implementation of interventions to support family care partners of persons living with dementia.…”
Section: Patient Centered Outcomes Research Institute (Pcori) In the mentioning
confidence: 99%
“…The widespread use of CABs as well as their composition, roles and responsibilities, and functions of CABs appear to reflect consensus regarding their importance and prominence in translational research. In a recent study of CTSAs utilizing CABs (Stewart et al, 2019), virtually every CAB included members "representing lay interests" (p. 220), such as community members, representatives of advocacy organizations, and patients. Approximately threequarters of CTSAs included clinicians and representatives of health-care organizations and almost one-third included government (e.g., local, state, federal) and academic representatives.…”
Section: Community Engagement and Community Advisory Boardsmentioning
confidence: 99%